رسالة في علم النحو، ورسالة في علم البيان، للشيخ عبدالله النبراوي "ت. 1275 هـ.": دراسة وتحقيق - النبراوي، عبدالله محمد، ت. 1275 هـ.; إبراهيم، إسراء صلاح خليل (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2023)
تعد المخطوطات التراثية في علوم العربية وغيرها من الكنوز الثمينة المفيدة التي خلفها أسلافنا العلماء للأجيال اللاحقة، لذا يقوم هذا البحث على دراسة وتحقيق أحد تلك المخطوطات والتي تختص بعلم النحو وعلم البيان، إذ تضمن البحث دراسة عن المخطوط وصاحبه، ومن ثم تحقيق لنص المخطوط، فقد اقتضت طبيعة البحث أن يقسم على قسمين: القسم الأول للدراسة والقسم الثاني للتحقيق. أما القسم الأول فانقسم على فرعين: تضمن الفرع الأول الحديث عن سيرة الشيخ النبراوي، وكان الحديث عنه بشكل مختصر؛ بسبب قلة ما ورد عنه في كتب التراجم. أما الفرع الثاني والذي تضمن دراسة المخطوط فقد اشتمل على التحقق من عنوان المخطوط، ونسبته إلى صاحبه، ودوافع تأليفه، ومنهجه، ووصف نسخ المخطوط، والمنهج المتبع في التحقيق. أما القسم الثاني الخاص بالتحقيق فقد تضمن نص المخطوط (رسالة في علم النحو، ورسالة في علم البيان) والذي اتبعت فيه الأصول المعتمدة في تحقيق المخطوطات، إذ تضمن كتابة المخطوط بالخط النسخي الحديث مع الالتزام بعلامات الترقيم، وتحرير النص على وفق القواعد الإملائية المعاصرة، وتخريج النصوص من مصادرها، والتعليق على بعض الفقرات التي تحتاج إلى شرح وتفصيل، وهذا العمل وضعته في الهامش؛ للحفاظ على النص كما أراده مؤلفه. The heritage manuscripts in Arabic sciences and other valuable and useful treasures that our ancestors left for later generations, so this research is based on the study and achieving one of those manuscripts, which is concerned with the knowledge of the statement, as the research included astudy of the manuscript and its owner, and then achieve the text of the manuscript the nature of the research required that it be divided into two parts. The first part is for studying and the second part is for investigation. As for the study section it was divided into two branches: the first branch included talking about the biography of sheikh AL-Nabrawy, talking about him was brief dueto the lack of what was mentioned about him in thw books of translations. As for the second branch, which includes the study of the manuscript, it included verifying the title of the manuscript , its attribution to its author, the motives for its author ship, its methodology, adescription of the copies of the manuscript, and the method used in th investigation. As for the second section related to the investigation, it included the text of the manuscript ( atreatise on grammar and atreatise on rhetoric) in which the approved principles were followed in the investigation of themanuscrips, ensures the writing of the manuscript in the modernization of write and punctuation, and editing the text on the contemporary spelling, and naskhi script with adherence to punctuation marks, extracting texts from their sources, introducing the flags mentioned in the manuscript text, and graduating text from their sources, and clarify some paragraphs that need explanation and elaboration. This work I put it in the margin to preserve the text as wanted by its author.
Keywords: اللغة العربية -- المخطوطات التراثية -- النحو العربي -- علم البيان